Alternative topical anesthesia for bronchoscopy in a case of severe lidocaine allergy. (2018) - Hensley, Matthew; Singer, Benjamin H.
Abstract: Lidocaine allergy presents a unique difficulty for both patients and providers who undergo/perform bronchoscopy. We present a case of a 73 yo male with severe lidocaine allergy who successfully underwent bronchoscopy with chloroprocaine topical anesthesia and discuss alternative topical anesthetic agents that may be used in this special situation.